Chance or Challenge for Fintech in SEA - Shi, Jianzheng; Wang, Yue (Eximia, 2023)
This article provides a comprehensive overview of the financial technology (fintech) landscape in Southeast Asia, highlighting the region's rapid economic growth and burgeoning e-commerce sector. It discusses the significant differences in population, economy, and culture among Southeast Asian countries, but recognizes the consistent need for enhanced modern financial services. Aspects such as the rapid development of internet infrastructure and new economy sectors have provided a fertile ground for the growth of fintech services such as mobile payments and online lending. The paper also examines the role of established economic centers like Singapore, alongside emerging markets like Indonesia and the Philippines. Further, it stresses the importance of understanding local policies, fostering local relationships, and integrating into local cultures for fintech firms looking to expand into these markets.